The Sardinia Radio Telescope: A comparison between close-range photogrammetry and finite element models. (May 2017) - Buffa, Franco; Causin, Andrea; Cazzani, Antonio; Poppi, Sergio; Sanna, Giannina; Solci, Margherita; Stochino, Flavio; Turco, Emilio
The Sardinia Radio Telescope (SRT), located near Cagliari (Italy), is the world's second largest fully steerable radio telescope endowed with an active-surface system. Its primary mirror has a quasi-parabolic shape with a diameter of 64 m. The configuration of the primary mirror surface can be modified by means of electro-mechanical actuators. This capability ensures, within a fixed range, the balancing of the deformation caused, for example, by loads such as self-weight, thermal effects and wind pressure. In this way, the difference between the ideal shape of the mirror (which maximizes its performances) and the actual surface can be reduced. In this paper the authors describe the characteristics of the SRT, the close-range photogrammetry (CRP) survey developed in order to set up the actuator displacements, and a finite element model capable of accurately estimating the structural deformations. Numerical results are compared with CRP measurements in order to test the accuracy of the model.